A New Therapeutic Community: Development of a Compassion‐Focussed and Contextual Behavioural Environment. (14th April 2014) - Veale, David; Gilbert, Paul; Wheatley, Jon; Naismith, Iona
<x xml:space="preserve">Abstract</x> Social relationships and communities provide the context and impetus for a range of psychological developments, from genetic expression to the development of core self‐identities. This suggests a need to think about the therapeutic changes and processes that occur within a community context and how communities can enable therapeutic change. However, the 'therapeutic communities' that have developed since the Second World War have been under‐researched. We suggest that the concept of community, as a change process, should be revisited within mainstream scientific research. This paper briefly reviews the historical development of therapeutic communities and critically evaluates their current theory, practice and outcomes in a systematic review. Attention is drawn to recent research on the nature of evolved emotion regulation systems, the way these are entrained by social relationships, the importance of affiliative emotions in the regulation of threat and the role of fear of affiliative emotions in psychopathology. We draw on concepts from compassion‐focussed therapy, social learning theory and functional analytical psychotherapy to consider how members of a therapeutic community can be aware of each other's acts of courage and respond using compassion. Living in structured and affiliative‐orientated communities that are guided by scientific models of affect and self‐regulation offers potential therapeutic advantages over individual outpatient therapy for certain client groups. This conclusion should be investigated further. Copyright © 2014 John Wiley & Sons, Ltd. Key Practitioner Message Current therapeutic community practice is not sufficiently evidence based and may not be maximizing the potential therapeutic value of a community. Compassion‐focussed therapy and social learning theory offer new approaches for a therapeutic environment, involving an understanding of the role, nature and complexities of compassionate and affiliative relationships from staff and members, behavioural change guided by learning theory, a clear formulation based on threat‐derived safety strategies, goal setting and positive reinforcement.